Analysis of goal scoring pathway for the winners in UEFA Champions League competition - Ahmad, M. F.; Zukhi, N. A. M.; Radzi, J. A.; Othman, N.; Azmi, A. M. N.; Mustafa, M. A.; Malek, N. F. A.; Vasanthi, R. K. (International Journal of Human Movement and Sports Sciences, 2023)
In soccer, goal scoring becomes the main factor in distinguishing between the winning and losing teams. One of the most crucial components of a soccer team's offensive performance is the goal-scoring path since it has been correlated with a higher likelihood of winning games. Therefore, the study aims to investigate the pathway of goal scoring among the winning teams in the previous seven consecutive seasons (2015/2016 - 2021/2022) in the UEFA Champions League competition. A total of 216 goals from the UEFA Champions League competitions in seven prior seasons (2015/2016 - 2019/2020) were examined. The pathway of goal scoring has been divided into long sequence passing, short sequence passing, and others. All the data have been recorded by using hand notational analysis and analyzed by using one-way ANOVA. A total of 216 goals were scored throughout the competition showing that 108 goals were from long sequence passing, 57 goals were from short sequence passing, and 51 goals came from others. The result indicated that there was a significant difference in the goal scoring sequence toward goal success among the winners, p > 0.00 which showed long sequence passing had the highest amount of goal scoring. As a summary, this demonstrated that the winning teams in 7 consecutive seasons of the UEFA Champions League competition (2015/2016 - 2021/2022) used long sequence passing frequently as their main attacking style to score a goal, which directly led them to win the championship. Therefore, the findings of this study may also be useful to coaches for educational reform in the soccer sports since they may allow them to make predictions about the best team tactics and goal-scoring strategies. It is suggested that future research examine teams of varied rankings to determine how goals are scored differently on each side.